Boosting Digital Health Engagement Among Older Adults in Hong Kong: Pilot Pre-Post Study of the Generations Connect Project - Aaron Wan Jia He; Runqi Yuan; Tzu Tsun Luk; Kelvin Man Ping Wang; Sophia Siu Chee Chan (JMIR Formative Research)
Abstract BackgroundOlder adults’ utilization of digital health care remains low despite a high demand for regular health services. Easily accessible eHealth interventions designed for older adults are needed. ObjectiveThis study aimed to examine the feasibility and effectiveness of an intergenerational, home-based eHealth literacy intervention package on older adults in Hong Kong. MethodsIn this study, 101 older adults (n=64, 63.4% female) with a median age of 80 (IQR 77-85) years received an intergenerational, home-based eHealth literacy intervention package, delivered by trained university student interventionists. The intervention (median 60, IQR 40.8-70 minutes) included personalized guidance on using mobile health apps, QR code scanners and instant messaging, and access to online health information, along with recommendations for physical and mental well-being. Following the intervention, a daily health-coaching message was sent to older adults via WhatsApp for 14 days. eHealth literacy, health, and lifestyle were assessed at baseline and at a 2-week follow-up using paired t ResultsRetention rate for the 2-week follow-up was 70.3% (71/101). Compared to baseline, eHealth literacy scores increased by 2.39 points (PdPd ConclusionsThe intergenerational, home-based eHealth literacy intervention package was feasible and acceptable, showing promise for increasing older adults’ engagement with digital health care resources and promoting healthy behaviors. Future studies should explore longer-term effects and ways to further improve the intervention.